Antibiotic susceptibility profiles of Mycoplasma bovis strains isolated from cattle in Hungary, Central Europe - Sulyok, Kinga M; Kreizinger, Zsuzsa; Fekete, Lilla; Hrivnák, Veronika; Magyar, Tibor; Jánosi, Szilárd; Schweitzer, Nóra; Turcsányi, Ibolya; Makrai, László; Erdélyi, Károly; Gyuranecz, Miklós (BMC veterinary research, 2014)
BACKGROUND: Mycoplasma bovis is a worldwide pathogen, causative agent of pneumonia, mastitis, arthritis, and a variety of other symptoms in cattle. The economic losses due to mycoplasma pneumonia could be reduced by antibiotic treatment. The aim of the present study was to determine the in vitro susceptibility of M. bovis strains isolated from cattle in Hungary to eleven antibiotics. RESULTS: Minimal inhibitory concentration (MIC) values of 35 M. bovis strains collected from different parts of Hungary between 2010 and 2013 were determined by the microbroth dilution method. Strains with high MIC values were found in the case of all applied antibiotics. The most effective antibiotics tested in vitro were fluoroquinolones (MIC₉₀danofloxacin 0.312 μg/ml, enrofloxacin 0.312 μg/ml, marbofloxacin 0.625 μg/ml). Our results confirm the observations of increasing MIC values to antibiotics commonly used in the therapy of mycoplasma infections, primarily to tetracyclines; tetracycline (MIC₉₀16 μg/ml) and oxytetracycline (MIC₉₀ ≥ 64 μg/ml) and macrolides; tylosin (MIC₉₀ ≥ 128 μg/ml) and tilmicosin (MIC₉₀ ≥ 128 μg/ml). The growth of many M. bovis strains was not inhibited by gentamicin (MIC₉₀8 μg/ml), spectinomycin (MIC₉₀ ≥ 256 μg/ml), florfenicol (MIC₉₀8 μg/ml) or lincomycin (MIC₉₀ ≥ 64 μg/ml). CONCLUSIONS: Our results emphasize the necessity of periodic testing for antibiotic susceptibility in this geographic region. Based on our in vitro examinations, fluoroquinolones could be the most effective drugs for the therapy of M. bovis infections in Hungary. However, current antimicrobial use policies have to be taken into account to avoid further antibiotic resistance development and to reserve fluoroquinolones for the treatment of severe infections which have responded poorly to other classes of antimicrobials.